Near-Earth Asteroids as Possible Parent Bodies of Meteor Streams - M.G. Sokolova; M.V. Sergienko (Учёные записки Казанского университета: Серия Естественные науки)
The genetic relationship of meteor streams with near-Earth asteroids (NEAs) is being actively studied. A genetic link with the asteroid is possible only for streams in which meteoroids have the geocentric speed smaller than 50 km/s, thereby meaning the proportionality of their orbits with the orbits of asteroids. To date, there are about 40 such orphan streams with unknown parent bodies.